The Role of Islamic Religious Education Teachers in Overcoming the Negative Impact of Tiktok Use on Childrens Character - Firdiana, Linda; Fatimah, Meti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
pThe rapid development of social media, particularly TikTok, has had a significant impact on childrens character, including emotional, moral, and social aspects. This article discusses the negative impacts of TikTok use on childrens character development and highlights the strategic role of Islamic Religious Education teachers in addressing these influences. A literature review found that excessive TikTok use can trigger emotional instability, decreased focus on learning, addictive behaviour, imitation of immoral content, and decreased self-confidence due to unrealistic social standards. In addressing this phenomenon, Islamic Religious Education teachers have a crucial role as character mentors, digital literacy facilitators, role models of Islamic values, and collaborative partners for parents and the school community. Possible measures include integrating character education into Islamic Religious Education learning, developing digital ethics, assisting students in selecting content, and strengthening religious activities as a form of internalising Islamic values. This article emphasises that character development in the digital era requires a holistic approach that combines moral education, digital literacy, and collaboration between schools and families to enable students to use social media wisely and ethically./p This article is also available at gb777